Variación en el diseño hidráulico de alcantarillado pluvial en la ciudad de Barranquilla, bajo diferentes escenarios hidrológicos (2020)
Evaluating the variation of the hydraulic designs of an urban canal, from intensity, duration and frequency curves (IDF) for hydrological analysis, is susceptible of optimization if geolocated weighted models and uncertainty estimation methods are added. In the present work, the Rebolo stream in the city of Barranquilla, Colombia is analyzed. For this, reference scenarios are carried out using the IDF curve estimation method of the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM), with inputs from the Ernesto Cortissoz and Las Flores stations. In addition to considering a contrast scenario based on the Mejía (2017) model. The hydrological simulation is carried out with the HEC-HMS program using the SCS method. For the hydraulic simulation, HCANALES and HEC-RAS are used. As a result, the hydraulic design variation and cost differences were found. The data scenario from the Ernesto Cortissoz station being the one with the least variability and uncertainty. It is concluded that the Mejía (2017) model is a useful tool to optimize the calculation of hydrological analysis and hydraulic design. To estimate the uncertainty and apply the GLUE method, it is necessary to measure flow data.